The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1557/proc-676-y4.6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Catalytic Methane Oxidation Over Pd Supported on Nanocrystalline CeO2: Effects of Calcination and Pd Loading

Abstract: The catalytic oxidation of methane was studied over palladium supported on nanocrystalline ceria. Three palladium weight loadings (1, 5, and 10 wt%) were tested after calcining at 500 °C, at 280 °C and after no calcination at all. For the 5 and 10 wt% loadings, the 280 °C-calcined and non-calcined catalysts exhibit enhanced activity after several heating and cooling cycles. Calcining these same catalysts at 500 °C results in a systematic decline in activity. For all pretreatments the 1 wt% Pd catalyst exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For several systems it was found that the influence of the substrate material on the catalytic performance in gas reactions, such as complete oxidation of methane, can be quite drastic. [30][31][32] Another application of the surface reactivity of nanocrystalline oxides is in gas sensing devices.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…For several systems it was found that the influence of the substrate material on the catalytic performance in gas reactions, such as complete oxidation of methane, can be quite drastic. [30][31][32] Another application of the surface reactivity of nanocrystalline oxides is in gas sensing devices.…”
Section: Nanoparticlesmentioning
confidence: 99%